FESTIVALS AND SUSTAINABILITY IN HUNGARY – THE STUDY AND PRESENTATION OF THE ASPECTS OF SUSTAINABILITY IN SELECTED HUNGARIAN FESTIVALS - Katalin LŐRINCZ; Ildikó ERNSZT; János CSAPÓ (Geo Journal of Tourism and Geosites, 2022)
Realizing the importance of festivals as a segment of the Hungarian cultural tourism market, the authors, after the theoretical review of the most important pillars of sustainability (economic, social-cultural and environmental), design the factors which establish the realization of the principles of sustainability in practice. Therefore such Hungarian festivals are analysed where during the organization and actuation, it is distinctly important to take into consideration the aims and principles of sustainability. The three analysed festivals represent different characteristics and supply and are important representatives of the Hungarian festival market. The authors chose these festivals as case studies because of several reasons: first of all the examined festivals address different target groups, furthermore, their themes and topics (supply) are also different; meanwhile all of them have communicated sustainability aspirations during their organisation and implementation. Data were primarily collected in 2020 and 2021 as an exploratory research based on content analysis of the web pages of the festivals. Parallel with this, structured interviews have been carried out with the organisers of the festivals. The analysed festivals were chosen based on their thematic approachThe authors believe that the analysis of these Hungarian good practices can serve as a design for other Hungarian and international festivals alike. The results of this investigation show that festivals mediating the elements of sustainability have already appeared in Hungary and the progress of the place and role of sustainability in event organization is applied in the country in an increasing extent serving as good examples for the non-sustainable events as well.